Regulatory Chill sebagai Konsekuensi Ancaman ISDS terhadap Negara - Desi Yanti Yohanes Lauw; Putri Batari Widyadhana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Public policies in the fields of health, environment, and safety are increasingly subject to disputes through the Investor-State Dispute Settlement (ISDS) mechanism. However, state efforts to protect the public often face claims from investors who consider themselves harmed. This situation carries serious consequences, as states not only bear high litigation costs but may also be required to pay significantly larger compensation if they lose the dispute. This gives rise to regulatory chill, a condition in which governments delay, weaken, or revoke regulations due to concerns over potential investment disputes. Even when some cases result in a state victory, the potential for regulatory chill remains significant, as investors do not need to win disputes to create regulatory uncertainty and pressure policymakers. This phenomenon can manifest in three forms precedential chill, anticipatory chill, and specific response chill, each affecting the policy-making process differently. Regulatory chill narrows the regulatory space, limits state capacity to protect public interests, and creates a deterrent effect on the implementation of new regulations. Using a normative juridical approach enriched with comparative case studies, this paper examines three primary sources of regulatory chill: the economic burden of arbitration and potential compensation, long-term commitments, and institutional limitations in meeting the standard of fair and equitable treatment.